Unusual complications of a common disease in COVID times: a case series - Kaur, Avneet; Chawla, Avneet Singh; Sangtam, T. Lirangla; Himaja, Mandalapu; Sewalia, Pooja (International Surgery Journal, 2021)
Acute appendicitis is the most common abdominal surgical emergency worldwide. 20-30% of cases of appendicitis can complicate which is defined as perforation, purulent peritoneal collection, abscess formation and generalized peritonitis. The risk of perforated appendicitis increases when appropriate treatment for acute appendicitis is delayed. There has been an avoidance of both urgent or emergency and routine medical care because of Coronavirus disease 2019 (COVID-19) concerns all over the world. In our study, the delayed presentation of the patients with acute appendicitis to the hospital prevented appropriate management leading to a much more morbid disease course. Increasing accessibility of medical and telehealth services might help prevent delay of needed care. Even during the COVID-19 pandemic, persons experiencing a medical emergency should seek and be provided care without delay.